PENGARUH PENERAPAN BERBAGAI BAHAN SEBAGAI MULSA TERHADAP LINGKUNGAN TUMBUH PADA TANAMAN FAMILI Solanaceae - Abdillah, Muhammad Helmy (AGRORADIX : Jurnal Ilmu Pertanian, 2023)
Crop yields can be increased by the agronomic practice of mulching. Mulching influences the microclimate of roots and keeps the soil physically stable from exposure to sunlight and moisture. Despite using a variety of substances, mulching, in theory, just safeguards the soil's surface. Mulch is supposed to be able to function by using certain plant biomass that is hard to degrade. In the Barito Kuala District, biomass such as empty oil palm, water hyacinth, and apu wood signs are freely accessible, however, these resources are not well used for farming. The aim of this study was to identify the mulch type that can inhibit weed development, limit soil temperature rises, and preserve soil moisture content. Using a randomized block design and patterned random sampling, this study was carried out in Sidomakmur Village, Batola Regency, from January to May 2023. The BNT 5% model was used for the data analysis. There were four different types of treatments used: no mulch (M0), mulch covered in silver-black plastic (M1), mulch made from empty oil palm bunches (M2), mulch made from water hyacinth (M3), and mulch made from water lettuce (M4). According to the findings, mulching lowered soil heat, restricted weed development by 98% compared to no mulching, and kept soil moisture content above the permanent wilting threshold index. The best treatment to reduce temperatures in the soil and suppress the growth of weeds had mulching using empty palm oil bunches.